The Use of Learning Videos to Improve the Skills in Writing Environmental Observation Results for Class II Students - Rahmita, Riska (Universitas Sebelas Maret, 2020)
This research has the aim of increasing the skills to write reports on the results of simple environmental observations. The subjects of this study were class II SD Negeri 2 Kritig, totaling 15 students. This research was conducted in 3 cycles. Each cycle consists of 4 stages, namely planning, implementing and observing, and reflecting. There are two assessments carried out in this study, namely an assessment of the content of the report and an assessment of the writing. The results of his research for the assessment of report content in the first cycle of completeness reached 80% and increased in cycles II and III to reach 100%. Then for the written assessment, completeness reached 26.67% in the first cycle increased to 67% in the second cycle and 86.7% in the third cycle. Furthermore, the average final score in cycle I reached 73.99, increased to 78.75 in cycle II and reached 80.2 in cycle III. So the conclusion is that through the use of instructional video media it can improve the skills of writing reports on environmental observations of grade II students of SD Negeri 2 Kritig.